2009
DOI: 10.1128/aac.01126-08
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Stability of Voriconazole Eye Drop Solution

Abstract: The combined systemic and topical administration of voriconazole has successfully been used to treat keratomycosis. Because no voriconazole eye drop product is commercially available, we prepared a sterile eye drop solution (10 mg/ml). Voriconazole remains stable over 30 days, providing an eye drop solution suitable for use for the topical treatment of fungal keratitis.Voriconazole is a recent triazole antifungal agent that is highly effective against Aspergillus, Fusarium, and Candida species. Furthermore, vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 13 publications
4
32
0
1
Order By: Relevance
“…amphotericin B, fluconazole, mitomycin, and voriconazole [123][124][125][126]. A sterile product with the active substance (i.e.…”
Section: Aseptic Handlingmentioning
confidence: 99%
“…amphotericin B, fluconazole, mitomycin, and voriconazole [123][124][125][126]. A sterile product with the active substance (i.e.…”
Section: Aseptic Handlingmentioning
confidence: 99%
“…Administered at a concentration of 1 mg/ml, it was effective in the treatment of keratitis by Candida, Aspergillus, Fusarium, Scedosporium, and Paecilomyces, among others (97)(98)(99)(100)(101) . Its advantages compared to polyenes include its greater stability to light and temperature, remaining effective for up to 30 days (102,103) . Studies in horses showed drug penetration even with epithelial integrity (104) .…”
Section: -Fluconazolementioning
confidence: 99%
“…Voriconazole is stable under regular storage temperatures (+4°C and room temperature), and exposure to light does not cause its degradation [5]. Voriconazole, intrastromal injection and/or eye drops , was started as soon as the diagnosis was confirmed both clinically and by smears and/or cultures, along with topical antibiotic eye drops (moxifloxacin hydrochloride 0.5%) to treat any associated bacterial infection and topical mydriatic cycloplegic eye drops (atropine sulphate 1%) along with systemic non-steroidal anti-inflammatory drugs.…”
Section: Clinical and Experimental Ophthalmologymentioning
confidence: 99%